Renal lipid accumulation induced by high-fat diet regulates glucose homeostasis via sodium-glucose cotransporter 2 - Chen, Juan; Li, Tingting; Vladmir, Carvalho; Yuan, Yang; Sun, Zilin (Diabetes research and clinical practice, 2021)
Visceral lipid accumulation is involved in a variety of physiological aberrations. In the current study, we aimed to investigate whether lipid accumulation had an impact on glucose reabsorption in the kidney. We examined renal lipid content and renal threshold for glucose (RTG) of each subject. We compared sodium-glucose cotransporter 2 (SGLT2) and sterol regulatory element-binding protein 1c (SREBP1c) levels in kidneys between rats fed with high fat diet (HFD) and normal chow diet. In vitro, HK2 cells were treated with palmitic acid (PA). Intracellular lipid droplet deposition, glucose uptake, SGLT2 and SREBP1c expression were examined. Renal fat fraction was positively associated with RTG among the recruited subjects. Moreover, renal lipid content was significantly increased in HFD rats, as well as SGLT2 expression. Accompanied with lipid droplet deposition in HK2 cells, PA stimulated SGLT2 expression and glucose uptake. In addition, after PA treatment, SREBP1c expression was significantly enhanced. However, transfection with siRNA-SREBP1c resulted in significant amelioration of lipid accumulation induced by PA in HK2 cells. Further examination indicated that accompanied with improvement of lipid deposition, SGLT2 expression and glucose uptake were attenuated. The results of our study demonstrate the involvement of renal lipid accumulation in glucose homeostasis.